Producing a new website for a paediatric liaison mental health team with our service users. Issue 4 (13th November 2020) - Adams, Alexander; Davies, Virginia; Stubbs, Bethany
Abstract : Introduction: Online resources are an important source of information about mental health issues and services for children and young people. Our service's website had an out-of-date appearance and was aimed at professionals. More importantly, comments in our routinely collected patient experience data indicated that service users did not know what to expect when coming to our service. Methods: We followed the model for improvement by testing out changes in plan, do, study and act cycles that included a review of recently updated child and adolescent mental health services' and youth charities' websites, designing a new web page for our service and then testing out the website in focus groups. We used routinely collected patient experience data to assess impact on wider patient satisfaction. Results: Focus groups involving patients, parents and professionals judged the new website to be clearer, more attractive and easier to understand. Routine patient experience data did not reveal any website-specific feedback. Conclusion: This study demonstrates that it is easy and possible to create an attractive and accessible website for a mental health service using quality improvement methodology. In order to capture and integrate ongoing feedback about a service's website from service users, routinely collected patient experience measures would need to ask specific questions related to this area. In this study, preproject and postproject patient experience data did not generate any specific comments.